Fabrication of a Visual pH Indicator Based on Cellulosic Materials and Anthocyanin Dyes Extracted from Red Cabbage - Nguyen, Ngoc Thang; Pham, Duc Duong; Vo, Thi Lan Huong (Old Journal, 2018)
In this paper, the anthocyanin compounds from Red cabage were extracted by ultrasound-assisted extraction (UAE) technology using acid-ethanol solvent. These natural colorants were immobilized to a non-woven cellulose membrane and a cellophane film using exhaust dyeing method. The anthocyanin extract solutions and cellulosic films loaded with anthocyanin colorant showed visibly distinct colors at all pH range from 1 to 13. The ultraviolet-visible (UV-Vis) spectrum of anthocyanin extract solutions showed a red shift of the maximum peak absorbance to longer wavelengths at higher pH-values, which indicates that chemical structure of anthocyanins have been altered. An application test was conducted for potential use of these dyed films as soybean milk spoilage sensors. The pH-sensing films showed pH changes and spoilage point of soybean milk samples, changing from violet to red. Therefore, the use of these colorimetric pH-sensing films as a diagnostic tool for the detection of food spoilage is a promising path.